I'm a potty princess [videorecording (DVD)] - Mazzarella, Tony; Mazzarella, Mark; Leigh, Katie; Pongracz, Michael (Mazzarella Media, 2011)
An animated tale about the toilet training of a little princess teaches toddler girls the proper skills and behaviors when using the potty for the first time. Includes songs and live-action activities.